(untitled) (LEGAL DIALOGICA, 2025)
This study examines the application of police discretion in handling traffic accidents at the Makassar City Police Resort. The main focus of the study is to determine the implementation of police discretion based on Law Number 2 of 2002 Article 18 paragraph (1) concerning the Police, as well as the obstacles experienced by the Police in handling traffic accidents at the Makassar City Police Resort. This research and writing uses an empirical research method. This method is not prescriptive, but descriptive. This research was conducted directly at the Makassar City Police Resort Office as the focus of the study. The results of this study discuss the application of police discretion in handling traffic accidents at the Makassar City Police Resort in accordance with Law Number 2 of 2002 Article 18 paragraph (1). Discretion is carried out through a Restorative Justice approach, especially for minor cases, underage perpetrators, or single accidents, with settlements based on peaceful agreements. Implementation procedures include handling at the scene, case analysis, and investigators’ decisions based on the principles of propriety, justice, and public interest. Benchmarks for discretion include legal compliance, office propriety, and respect for human rights. Implementation barriers are divided into internal factors such as limited human resources and legal understanding, as well as external factors such as public pressure and differences in perceptions between law enforcement agencies. This study examines the implementation of discretion by the Makassar City Police in enforcing the law fairly and humanely. It was found that officers’ lack of understanding of the limits of discretion and the principles of justice is a major obstacle. Therefore, it is recommended to increase the capacity of investigators through ongoing training and the implementation of a restorative justice approach. It is also necessary to develop detailed operational guidelines and carry out strong coordination with the prosecutor’s office, as well as public education. Discretion must be exercised professionally, accountably, and within the legal framework for the sake of substantive justice and respect for human rights. Abstrak: Peneltian ini mengkaji penerapan diskresi kepolisian dalam penanganan kecelakaan lalu lintas di Kepolisian Resor Kota Makassar. Fokus utama penelitian adalah untuk mengetahui pelaksanaan diskresi kepolisian berdasarkan Undang-Undang Nomor 2 Tahun 2002 Pasal 18 ayat (1) tentang Kepolisian, serta hambatan-hambatan yang dia alami pihak Kepolisian dalam penanganan kecelakaan lalu lintas di Kepolisian Resor Kota Makassar. Penelitian dan penulisan ini menggunkan metode penelitian empiris. Metode ini tidak bersifat preskriptif, melainkan deskriptif. Penelitian ini dilakukan secara langsung di Kantor Kepolisian Resor Kota Makassar sebagai lokasi fokus studi. Hasil penelitian ini membahas penerapan diskresi kepolisian dalam penanganan kecelakaan lalu lintas di Kepolisian Resor Kota Makassar sesuai dengan Undang-Undang Nomor 2 Tahun 2002 Pasal 18 ayat (1). Diskresi dilakukan melalui pendekatan Restorative Justice, terutama untuk kasus ringan, pelaku di bawa umur, atau kecelakaan tunggal, dengan penyelesaian berbasis kesepakatan damai. Prosedur pelaksanaan mencakup penanganan di tempat kejadian, analisis kasus, dan keputusan penyidik berdasarkan asas kepatutan, keadilan, serta kepentingan umum. Tolak ukur diskresi meliputi kesesuaian hukum, kepatutan jabatan, dan penghormatan HAM. Hambatan pelaksanaan terbagi atas faktor internal seperti keterbatasan SDM dan pemahaman hukum, serta faktor eksternal seperti tekanan masyarakat dan perbedaan persepsi antar lembaga penegak hukum. Penelitian ini membahas pelaksanaan diskresi oleh Kepolisian Resor Kota Makassar dalam penegakan hukum yang adil dan humanis. Ditemukan bahwa kurangnya pemahaman aparat terhadap batas diskresi dan prinsip keadilan menjadi hambatan utama. Oleh karena itu, disarankan peningkatan kapasitas penyidik melalui pelatihan berkelanjutan serta penerapan pendekatan Restorative Justice. Perlu juga disusun pedoman operasional yang rinci dan dilakukan koordinasi yang kuat dengan kejaksaan serta edukasi kepada masyarakat. Diskresi harus dijalankan secara profesional, akuntabel, dan dalam koridor hukum demi keadilan substantif dan penghormatan HAM.